KUALIFIKASI OPERATOR OPERASI SEBAGAI PEMODERASI PENGARUH KADAR HEMOGLOBIN DAN JENIS OPERASI PADA JUMLAH TES CROSS-MATCH DI BANK DARAH - Farida Farida; Wisnu Untoro (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2016)
The aims of research is to understand/discover the effect of the qualification of surgery operator for moderating pre-operative hemoglobin level at the patient and the type of operation performance (elective or emergency) with the number of cross-match test request for surgery preparation. The research utilizes the quantitative empirical method using a secondary data derived from the orthopedic hospital blood-bank Prof. DR. R. Soeharso Surakarta i.e. the number of data cross-match test request from June 2015 to May 2016 with 360 samples. The Data analysis method is Moderated Regression Analysis.The results of research exhibits significant direct influence pre-operative hemoglobin level and the type of operation to the number of cross-match test request. The qualification of surgery operator has not proven significantly as a moderation variable. The qualification of surgery operator influences simultaneously on the patient preoperative hemoglobin correlation level and type of operation to the number of cross-match test request, although no proven effect on an individual basis.